DIGITAL COMPETENCE IN THE CONTEXT OF LEARNING CONCEPTUAL ASPECTS IN HIGHER EDUCATION INSTITUTIONS - Vindača, Olga (Education Reform: Education Content Research and Implementation Problems, 2019)
Media and new technologies integration into the learning process of higher educational institutions stimulates the necessity for the development of digital competence. However, the evaluation of digital competence is required before working out and offering the new programs for the improvement of digital competence. This article will review the issue of digital competence focusing on the analyses of its evaluation instruments such as "Attitudes toward Information Technologies (IT) Scale" and "Self-appraisal form". It is the preliminary result of on going applied research of RTA Research Institute for Regional Studies (RIRS). The aim of this research is to adopt "A-IT Scale" to Latvian conditions and to define students and lecturers of Latvian higher educational institutions attitudes towards IT as the necessity for digital competence improvement in the context of learning conceptual aspects in higher education institutions.